Model for Harmonization of Islamic Higher Education Financing Policies and Governance - Nurdiyanti, Yanti; Nurhamzah, Nurhamzah; Iqbal, Aji Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to: 1) identify the financing and governance policies of Islamic Higher Education, 2) identify key factors that influence the harmonization of financing and governance policies, and 3) formulate a comprehensive harmonization model for Islamic higher education. This study was conducted at the Islamic University of Bandung (UNISBA) using a qualitative approach with a grounded theory method through in-depth interviews, observations, and documentation studies. Primary data were obtained from Foundation managers, university leaders, and related units, while secondary data came from institutional documents, financial reports, internal policies, statistical data, and academic literature. Data analysis was carried out using the Miles and Huberman technique and assisted by Atlas. ti. The results of the study indicate that: 1) UNISBA's financing governance is built through the division of autonomy between the Foundation as an asset manager and the university as an academic manager, with a centralized budgeting mechanism that ensures accountability. 2) There are six key factors that shape harmonization, namely diversification of funding sources, Islamic governance values, government support, a culture of philanthropy through BMU, entrepreneurial innovation and industrial partnerships, and institutional leadership and coordination. 3) A financing harmonization model that integrates institutional autonomy, proportion of fund allocation, optimization of various funding sources, and the principles of Good University Governance as a basis for sustainable and adaptive financing management.